Presymptomatic diagnosis of Fabry's disease: a case report. (December 2016) - Hasselbalch, Rasmus; Madsen, Per; Bundgaard, Henning; Theilade, Juliane
Abstract Background Fabry's disease is a rare X-linked genetic disorder characterized by reduced levels of the α-galactosidase A enzyme. It may present with a cardiac phenotype resembling hypertrophic cardiomyopathy. However, as a specific enzyme replacement therapy is available, it remains an important differential diagnoses in patients presenting with cardiac hypertrophy. In boys, onset has been reported in early childhood with complaints initially comprising neuropathic pain, reduced sweat production, and gastrointestinal symptoms. Later the cardiac, renal, and central nervous systems may become affected. Female mutation carriers may remain asymptomatic or present at a later age with varying symptoms and clinical manifestations due to random inactivation of the X chromosome in different organs. Case presentation Here we present a case of Fabry's disease diagnosed in the daughter of an elderly, Caucasian woman (81 years old) with late-onset cardiac conduction disease and heart failure. We discuss the implications of cascade screening relatives of elderly probands. Conclusions Irrespective of the patient's age, physicians must be on the lookout for phenocopies when identifying patients with possibly inheritable cardiomyopathies. The specific – precise – diagnosis may be crucial for the patient as well as the relatives.